Устройства считывания информации с крупноформатных матриц ИК-фотодиодов - Reva, V. P.; Marchishin, I. V.; Korinets, S. V.; Sizov, F. F. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
The research results are given for designed and manufactured readout devices for matrices of infrared photodiodes of formats 640×512 and 320×256. The article comments the architecture of reading circuit diagramming and its influence on the parameters of the FPU, the design of interfaces with an infrared photodiodes, the design of the reading circuit of the information charge, the influence of the geometric dimensions of the matrix elements on the output parameters of readout devices. A comparison of calculated and measured parameters of readout devices has been carried out.